Medalist. 1 - Tsurumaikada (Kodansha USA Publishing, LLC, 2024)
"Inori is a little girl who dreams of becoming a figure skater. Yet, the obstacles to this dream feel insurmountable: Inori's already "too old" (she's 11); she's always had trouble at school; and, worst of all, her older sister's skating dreams ended in failure, so her mother is dead set against putting her other daughter through a similar experience. Still, the rink is the only place Inori can be herself, and she's out on the ice when a fateful meeting takes place. Tsukasa, a frustrated coach on the edge of giving up competitive skating himself, will join Inori to form an unstoppable duo powered by hard work, transcendent joy, and an unshakeable belief that they can prove everyone wrong"--Publisher's website.